The influence of particle size on the absorption rate of catfish (Clarias gariepinus) bone calcium - ADI, Annis Catur; VETERINY, Anna Surgean; SALISA, Wizara; AYU, Wilis Cahyaning; RACHMAWATI, Heni (Food Science and Technology, 2023)
The adequacy of calcium from food consumption is difficult to meet because of its low absorption rate. One of the ways to increase calcium absorption is to increase its solubility by decreasing its particle size to the nanometer scale. Nanoparticles have better performance due to their increased surface area-to-volume ratio. This study aimed to determine the effect of the particle size of fish bones on calcium absorption rate. The catfish bone flour was made by two methods with the same stages, but they differed in the use of tools (the machine method and the traditional method). The particle size analysis of the flour showed that the machine method was in the nanometer range. The nutritional content of the machine-milled flour was rich in protein and lipids, while the flour produced by the traditional method was rich in calcium, phosphorus, and carbohydrates. Based on the results of the absorption test, both catfish bone flours were proven to be able to gradually increase calcium levels to their peak at 2 h post-administration. In sum, bone flour with nanoparticle sizes produced by the machine was able to maximize the calcium absorption rate in rats.